Exploiting Expression of Hippo Effector, Yap, for Expansion of Functional Islet Mass - George, Nicholas M. (Mol Endocrinol, 2015)
Loss of pancreas β-cell function is the precipitating factor in all forms of diabetes. Cell replacement therapies, such as islet transplantation, remain the best hope for a cure; however, widespread implementation of this method is hampered by availability of donor tissue. Thus, strategies that expand functional β-cell mass are crucial for widespread usage in diabetes cell replacement therapy. Here, we investigate the regulation of the Hippo-target protein, Yes-associated protein (Yap), during development of the endocrine pancreas and its function after reactivation in human cadaveric islets. Our results demonstrate that Yap expression is extinguished at the mRNA level after neurogenin-3-dependent specification of the pancreas endocrine lineage, correlating with proliferation decreases in these cells. Interestingly, when a constitutively active form of Yap was expressed in human cadaver islets robust increases in proliferation were noted within insulin-producing β-cells. Importantly, proliferation in these cells occurs without negatively affecting β-cell differentiation or functional status. Finally, we show that the proproliferative mammalian target of rapamycin pathway is activated after Yap expression, providing at least one explanation for the observed increases in β-cell proliferation. Together, these results provide a foundation for manipulating Yap activity as a novel approach to expand functional islet mass for diabetes regenerative therapy.